El liderazgo educativo en los docentes y el rendimiento escolar de los estudiantes de E.G.B. en la Unidad Educativa “Juan de Velasco” del cantón Riobamba, provincia de Chimborazo, período académico 2020 - 2021 - Delgado Cárdenas, María Elena (2022)
The lack of educational leadership on the part of the teacher is an important factor that, as the main problem, hinders the significant learning of children, directly affecting their school performance. The objective of this study is to understand the relationship between the educational leadership of teachers in the school performance of basic general education students in the "Juan de Velasco" educational unit. The theoretical foundation contemplates aspects, criteria on educational leadership which plays a very important role in educational quality, since it is the key piece in the framework to develop high school performance of students, methodologically it had a mixed approach with a non-experimental design and a field and bibliographic study, descriptive-explanatory type with methods; scientific, deductive, analytical, synthetic inductive, the population was 500 students and 22 teachers, its sampling was probabilistic, from which the sample consisting of 96 students and 4 teachers was obtained through a statistical formula. Two instruments were used for data collection; the interview to the teachers and a survey to the students with 12 items of closed type. The findings of this research reflect that teachers must know and know the importance of a good educational leader in the classroom, it is not practiced daily in favor of educational needs. Reason why, a proposal was made based on strategies that motivate the development of a good teacher leader and improve the school performance of students.